(untitled) (Research, Society and Development, 2022)
The lipodystrophic syndrome in HIV is characterized by alterations in the distribution of body fat and metabolic alterations characterized by an increase in serum lipids; peripheral insulin resistance. The questionnaires applied were: a questionnaire to characterize adults with HIV/AIDS. The majority of respondents were male (66%), aged between 29 and 73 years old, with regard to education, 44% had completed high school. They were predominantly of low socioeconomic status. As for marital status, only 14% were married. As for the lipid variables, the mean total cholesterol levels in males (190.51 mg/dl) were higher than in females (189.16 mg/dl), but with a difference of only 1.35 mg/dl. dl, which makes a difference of little impact to the search. As for the triglycerides rate, the male average was 199.18 mg/dl, a value above the reference value limit established by the dyslipidemia guidelines, as well as the average value for females. The research has implications for professional practice, with the perception of the importance of observing, improving and intervening so that the demands of service users are met, aiming to direct actions aimed at their resolution and strengthening the patient’s bond with health, in addition to improving lipid rates, in order to reduce the risk of cardiovascular disease.